A comparative proteomic study of salt tolerance in Arabidopsis thaliana to identify strategies for improving salt tolerance in Solanum lycopersicum - Ahmed, Inshera; Juspy, Jakia Tahsin; Quader, Sultan Shanneedh (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.